The Irish potato famine pathogen Phytophthora infestans originated in central Mexico rather than the Andes - Goss, E.M.; Tabima, J.F.; Cooke, D.E.L.; Restrepo, S.; Fry, W.E.; Forbes, G.; Fieland, V.J.; Cárdenas, M.; Grunwald, N.J. (National Academy of Sciences, 2014)
The potato late blight pathogen was introduced to Europe in the 1840s and caused the devastating loss of a staple crop, resulting in the Irish potato famine and subsequent diaspora. Research on this disease has engendered much debate, which in recent years has focused on whether the geographic origin of the pathogen is South America or central Mexico. Different lines of evidence support each hypothesis. We sequenced four nuclear genes in representative samples from Mexico and the South American Andes. An Andean origin of P. infestans does not receive support from detailed analyses of Andean and Mexican populations. This is one of a few examples of a pathogen with a known origin that is secondary to its current major host.